Issues and challenges in special education: A qualitative analysis from teacher’s perspective - Allam, Fely C.; Martin, Matronillo M. (Southeast Asia Early Childhood Journal, 2021)
The general purpose of this study is to determine the issues and challenges of special education (SPED) teachers in teaching children with learning disabilities in the City Division of Ilagan Isabela, Philippines. The 15 SPED teachers were served as the respondents of this study using purposive sampling technique. Qualitative Research Method (QRM) was utilized to determine the issues and challenges of the teachers. Thematic analysis was employed to interpret the data. The analyses on the sharing of the key informants regarding their collective description of their challenges as SPED teacher led to the emergence of five distinct themes that include, choosing appropriate strategy and motivation; identifying individual needs; challenging but fulfilling; acceptance and patience; and respect one’s right. Most teachers teaching children with learning disabilities did not receive any special needs education training from the school, they feel that they are not qualified to teach the children with learning disability. Moreover, teachers assigned in SPED classes lack of strategies in dealing with learners with disabilities. This study revealed that the classrooms for children with learning disabilities in Division of Ilagan at large have poor learning environment to support the SPED such as lack of budget, curriculum guide, Instructional Materials (IMs) and even school facilities. It could be concluded that placement of learners with special needs in an inclusive classroom with ordinary learners is not enough with no proper support. Learners with disability did not receive all the necessary support and services for accessing the curriculum facilities; and stakeholders’ supports is very minimal to support the needs of the students enrolled in SPED classes. On the other hand, issues and problems were solved technically to sustain the positive working environment among school heads, teachers and stakeholders. The Department of Education Training and Development in collaboration with regional in service officers should organize continuous professional development opportunities on inclusion strategies of learners with SPED needs. The implementers of the SPED programs shall strictly adhere to the policies, and the strong support of the stakeholders shall be encouraged by formulating active organization spearheaded by the school head.